Urinary Titin Is Increased in Patients After Cardiac Surgery - Tanihata, Jun; Nishioka, Naritomo; Inoue, Takahiro; Bando, Ko; Minamisawa, Susumu (Frontiers in Cardiovascular Medicine, 2019)
Background: Few non-invasive biomarkers have been used to detect myocardial injury in patients with heart diseases. Recently, the N-terminal fragment (N-titin) of titin, a giant sarcomeric protein, which is involved in muscular passive tension and viscoelasticity, has been reported to detect muscle damage in patients with cardiomyopathy as well as in patients with skeletal muscle dystrophy and in healthy volunteers with endurance exercise. In the present study, we evaluated whether urinary N-titin is changed during a perioperative period and whether its increase reflects myocardial damage. Material and methods: In 18 patients who underwent cardiac surgery, blood and urine samples were obtained before and after surgery. We measured the urinary levels of N-titin with a highly sensitive ELISA system. Results: Urinary N-titin to creatinine (N-titin/Cr) was significantly increased in all patients postoperatively (43.3 ± 39.5 pmol/mg/dL on the day of operation) and remained significantly high for at least four days postoperatively. Urinary N-titin/Cr was positively correlated with serum cardiac troponin T (r=0.36, p=0.0006, n=90) but not creatine kinase-MB. We also found that urinary N-titin/Cr in patients after a coronary artery bypass grafting operation was higher by day 2 postoperatively than in patients following open heart surgery. Conclusion: The cleaved N-titin was significantly increased in urine after cardiac surgery. Urinary N-titin may be useful for detecting the risk of latent postoperative cardiac damage.